2015
DOI: 10.1007/s11046-015-9978-y
|View full text |Cite
|
Sign up to set email alerts
|

Candida nivariensis as a New Emergent Agent of Vulvovaginal Candidiasis: Description of Cases and Review of Published Studies

Abstract: Candida nivariensis is a new emergent agent related to human infections in the vaginal tract and other localizations, but the phenotypic characteristics are very similar to Candida glabrata and can be misidentified and underdiagnosed. We described four cases of vulvovaginitis identified by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry and confirmed the results with PCR amplification and sequencing of the entire ITS genomic region (ITS1, ITS2 and 5.8 rRNA). We reinforce the need f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…The strains were isolated from blood, bronchoalveolar lavage fluid (BALF) and urine of three patients over a 3-year study period (Alcoba-Flórez et al 2005). Current knowledge indicates that this species occurs worldwide and the number of published cases reaches 108 in Europe (Spain, the UK, France, Poland) (Borman et al 2008; Gorton et al 2013; López-Soria et al 2013; Parmeland et al 2013; Swoboda-Kopeć et al 2014; Aznar-Marin et al 2016; Angoulvant et al 2016), 31 in Asia (Japan, Indonesia, India, China, Malaysia) (Fujita et al 2007; Wahyuningsih et al 2008; Chowdhary et al 2010; Sharma et al 2013; Li et al 2014; Tay et al 2014; Feng et al 2015; Hou et al 2017), 11 in Australia (Lockhart et al 2009; Pinto et al 2011), four in Latin America (Argentina and Brazil) (Morales-López et al 2016; Figueiredo-Carvalho et al 2016) and one case in Africa (Burkina Faso) (Sanata et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The strains were isolated from blood, bronchoalveolar lavage fluid (BALF) and urine of three patients over a 3-year study period (Alcoba-Flórez et al 2005). Current knowledge indicates that this species occurs worldwide and the number of published cases reaches 108 in Europe (Spain, the UK, France, Poland) (Borman et al 2008; Gorton et al 2013; López-Soria et al 2013; Parmeland et al 2013; Swoboda-Kopeć et al 2014; Aznar-Marin et al 2016; Angoulvant et al 2016), 31 in Asia (Japan, Indonesia, India, China, Malaysia) (Fujita et al 2007; Wahyuningsih et al 2008; Chowdhary et al 2010; Sharma et al 2013; Li et al 2014; Tay et al 2014; Feng et al 2015; Hou et al 2017), 11 in Australia (Lockhart et al 2009; Pinto et al 2011), four in Latin America (Argentina and Brazil) (Morales-López et al 2016; Figueiredo-Carvalho et al 2016) and one case in Africa (Burkina Faso) (Sanata et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In one study, four isolates collected from vagina were identified as C. nivariensis by the Bruker MS system (Bruker Daltoniks), with a log score between 1.802 and 2.086 (Aznar-Marin et al, 2015). MALDI-TOF MS has been reported to have the ability to distinguish within the C. glabrata clade, i.e., between C. glabrata, C. nivariensis and C. bracarensis , with scores of <1.700 as C. nivariensis (3/10 strains) and C. bracarensis (1/1 strain; Pinto et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of quorum sensing molecules with natamycin against C. tropicalis haven been used successfully by researchers (Agustín et al, 2019). However, the number of cases is low possibly due to the impossible phenotypic identification of C. glabrata (Aznar-Marin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%